Estimation of changes in the distribution of income in the Czech Republic mixture models - Malá, Ivana (Silesian Statistical Reviev, 2013)
In the text the development of distributions (and their characteristics) of the equivalised net annual nominal income in Czech households in 2004-2009 is studied. Three-parametric lognormal and Dagum distributions are used as a model for income probability distribution. Moreover, finite mixtures of these distributions are estimated for the models with an observable component membership (given by the number of economically active members of the household and the number of unemployed members). Data from the European Union survey – Statistics on Income and Living Conditions 2005-2010 – are used for the analysis. All the estimates in the text are obtained using the maximum likelihood method
Śląski Przegląd Statystyczny = Silesian Statistical Review, 2013, Nr 11 (17), s. 137-150
Keywords: income distributions; maximum likelihood estimate; finite mixture; lognormal distribution; Dagum distribution; rozkład dochodów; estymacja metodą największej wiarygodności; rozkład log-normlany; rozkład Daguma